Checklist of the Carnivorous Snail Superfamily Streptaxoidea Gray, 1860 (Gastropoda: Eupulmonata) from Laos with Description of a New Species - Vanhdibay, Anny; Viennasai, Chathala; Mitthiyaphone, Patisith; Deuanemany, Chanthanom; Siriboon, Thanit; Inkhavilay, Khamla (Tropical Natural History, 2023)
The superfamily Streptaxoidea is widespread in the tropical region and represents a major portion of the land snail fauna of most Southeast Asian countries. Laos is located on one of the biodiversity hotspots in this region, with high mountain ranges and limestone karsts. Herein, an up-to-date checklist is provided of all known Streptaxoidea species recorded in Laos until the year 2022. This annotated checklist comprises 23 species (9 Diapheridae and 14 Streptaxidae) with brief taxonomic notes/remarks when necessary. Of these, Haploptychius somsaki Vanhdibay and Inkhavilay, sp. nov., is described based on shell morphological characters of specimens collected from the limestone karsts in central Laos. The species has an aperture oblique-ovate; peristome discontinuous, expanded, reflected, and thickened with enlarged columella fold adjacent to columellar axis. A systematic revision and more field research are required to fully reveal the species diversity of the superfamily Streptaxoidea in Laos.